2022
DOI: 10.1093/ijnp/pyac056
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia, Apathy, Pleasure, and Effort-Based Decision-Making in Adult and Adolescent Cannabis Users and Controls

Abstract: Background Cannabis use may be linked with anhedonia and apathy. However, previous studies have shown mixed results and few have examined the association between cannabis use and specific reward sub-processes. Adolescents may be more vulnerable to harmful effects of cannabis than adults. This study investigated (1) the association between non-acute cannabis use and apathy, anhedonia, pleasure, and effort-based decision-making for reward, and (2) whether these relationships were moderated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…This work, however, typically yields mixed results especially among adult users. For example, studies suggest that regular cannabis users are both less (Winters et al, 2022) and more agreeable (Vigil et al, 2022); while other studies suggest that chronic users have both low (Looby & Earleywine, 2007) and normal levels of motivation (Skumlien et al, 2023). We cannot help but wonder if one of the reasons for these mixed results is the implied goal of this research: to reduce use.…”
Section: The Chronicmentioning
confidence: 84%
See 1 more Smart Citation
“…This work, however, typically yields mixed results especially among adult users. For example, studies suggest that regular cannabis users are both less (Winters et al, 2022) and more agreeable (Vigil et al, 2022); while other studies suggest that chronic users have both low (Looby & Earleywine, 2007) and normal levels of motivation (Skumlien et al, 2023). We cannot help but wonder if one of the reasons for these mixed results is the implied goal of this research: to reduce use.…”
Section: The Chronicmentioning
confidence: 84%
“…While numerous studies suggest that chronic use is associated with apathy and low motivation (Pacheco-Colón et al, 2018), many of these associations disappear once analyses control for influential third variables like personality, depression, and alcohol use (Petrucci et al, 2020). Some studies find no relationship between chronic cannabis use on the one hand and apathy and objective effort willingness on the other hand (Skumlien et al, 2023). Remarkably, other studies suggest that chronic users are more-not less-motivated, when motivation is assessed via objective behavioral tasks and not simply subjective self-report (Vele et al, 2022).…”
Section: Emotions Motivation and Self-regulationmentioning
confidence: 99%
“…В свою очередь, последняя рассматривается в качестве фактора высокого риска суицидального поведения у данного контингента лиц [55]. В частности, обследование 274 пациентов с ПТСР с использованием стандартизированных шкал показало, что уровень потребления каннабиса коррелировал с выраженностью ангедонии [56]. При коморбидном злоупотреблении ПАВ закономерно нарастает социальная дезадаптация, что негативно влияет на прогноз и динамику выздоровления и приводит к повышению риска суицида.…”
Section: птср и суицидальность у представителей специфических групп п...unclassified
“…There are failures to find any effects of cannabis smoke or THC vapor exposures in male and female rats during adolescence using assays for cognition and anxiety-like behaviors [163,164]. In humans, moderate adolescent cannabis users have reported less anhedonia than nonusers [165]. Another study found no effect of moderate adolescent cannabis use on ventral striatum activity in a test of reward anticipation [166], again indicating the importance of considering dose in analyses of the effects of all drugs.…”
Section: Cannabismentioning
confidence: 99%